Uveal effusion syndrome – a case study - Grabska-Liberek, Iwona; Zagajewska, Katarzyna; Kosmala, Jacek (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
We report a case study of a 63-year-old female admitted to our department with substantially decreased vision in her right eye. Bilateral uveal effusion syndrome concomitant with nanophthalmos was diagnosed. The patient received systemic treatment with non-steroidal anti-inflammatory drugs and underwent sclerectomy with topical application of mitomicin C. Gradual resolution of the retinal detachment leading to full reattachment was observed over the next 2 months. Retinal detachment did not reoccur in a long-term follow up.